Influence of feeding and UVB exposition on the absorption mechanisms of calcium in the gastrointestinal tract of veiled chameleons (Chamaeleo calyptratus). Issue 6 (22nd May 2014) - Haxhiu, D.; Hoby, S.; Wenker, C.; Boos, A.; Kowalewski, M. P.; Lewis, F.; Liesegang, A.
Summary The purpose of this study was to investigate the influence of feeding and UVB exposition on the occurrence and distribution patterns of vitamin D receptors (VDR) and calbindin D28k (Cb‐D28k) in the gastrointestinal tract of veiled chameleons. Thus, 56 veiled chameleon hatchlings were divided into six treatment groups: UV (with UVB exposure); No (no supplements, no UVB exposure); CaAUV (with calcium (Ca), vitamin A supplementation, UVB exposure); CaA (with Ca, vitamin A supplementation); CaADUV (with Ca, vitamin A, vitamin D supplementation, UVB exposure); and CaAD (with Ca, vitamin A, vitamin D supplementation). Animals were reared under the suspected conditions for 6 months on locust‐based diets. Tissue samples of stomach, duodenum, ileum and colon were taken, and semi‐quantitative immunohistochemical methods (IHC) were performed to detect Cb‐D28k and VDR. VDR immunoreactions were higher in the luminal epithelium of the duodenum than in that of the ileum. VDR immunoreactions in the luminal epithelium were higher at the base of the villi of the duodenum as compared to the tip. Cb‐D28k immunoreactions were mainly observed in the luminal epithelium of the duodenum. The two groups treated with all dietary supplements (CaADUV, CaAD) exhibited a higher Cb‐D28k immunoreaction as those with no supplements and UVB exposure only. No immunoreaction for both proteins could be detected in the stomach. This study suggests that the duodenum plays an important role in the active transcellular absorption of Ca in veiled chameleons as shown by the immunohistochemical detection of VDR and Cb‐D28k. Expression of Cb‐D28k, in particular, appears to be regulated by dietary supplementation of vitamin D and vitamin A. VDRs, however, tended to be upregulated when animals were not supplemented with Ca, vitamin D and vitamin A. This may be due to the decreased Ca concentrations which caused vitamin D activation in the skin without any supplementation, but UVB exposure.